2014
DOI: 10.1017/s0263574714001167
|View full text |Cite
|
Sign up to set email alerts
|

The effects of swing-leg retraction on running performance: analysis, simulation, and experiment

Abstract: Using simple running models, researchers have argued that swing-leg retraction can improve running robot performance. In this paper, we investigate whether this holds for a more realistic simulation model validated against a physical running robot. We find that swing-leg retraction can improve stability and disturbance rejection. Alternatively, swing-leg retraction can simultaneously reduce touchdown forces, slipping likelihood, and impact energy losses. Surprisingly, swing-leg retraction barely affected net e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Expanding this approach, researchers have demonstrated an optimal retraction rate for perturbation rejection [65] and energy efficient locomotion [66]. Additionally, modeling and experimental results using large bioinspired quadrupedal robots [65,67] indicate that swing leg retraction can potentially mitigate the risk of slippage at heel-strike during rapid running. Therefore, we test the effect of varying leg retraction period on locomotion and hypothesize (H 1 ) that increasing the leg retraction period reduces slipping and improves locomotion performance.…”
Section: Hypothesis One (H 1 )mentioning
confidence: 99%
“…Expanding this approach, researchers have demonstrated an optimal retraction rate for perturbation rejection [65] and energy efficient locomotion [66]. Additionally, modeling and experimental results using large bioinspired quadrupedal robots [65,67] indicate that swing leg retraction can potentially mitigate the risk of slippage at heel-strike during rapid running. Therefore, we test the effect of varying leg retraction period on locomotion and hypothesize (H 1 ) that increasing the leg retraction period reduces slipping and improves locomotion performance.…”
Section: Hypothesis One (H 1 )mentioning
confidence: 99%
“…Previous research found that sliding between the foot and ground has to be controlled to avoid falling and slipping [34]. However, sliding is caused by the transverse force applied to the foot when it is in contact with the ground.…”
Section: Discussionmentioning
confidence: 99%
“…A biped walker [17] and passive quadrupeds [18,19] achieved gait transitions by only the body dynamics. Moreover, some results showed the functions of partial body dynamics for legged locomotion, including swing-leg retraction [20], compliant legs [21,22], and torsos [23]. Although the functions of partial body dynamics in animals were suggested in these studies, whole body dynamics is still entangled.…”
Section: Introductionmentioning
confidence: 99%